Extracellular Matrix Reorganization during Cryo Preparation for Scanning Electron Microscope Imaging of Staphylococcus aureus Biofilms. (4th July 2014) - Wu, Yong; Liang, Jing; Rensing, Kim; Chou, Tseng-Ming; Libera, Matthew
Abstract Biofilms are three-dimensional communities of bacteria distributed in a highly hydrated extracellular matrix (ECM). They can be visualized by scanning electron microscopy (SEM), but the requisite SEM sample preparation can modify the biofilm morphology. Here, four different approaches to prepare biofilms of hydrated Staphylococcus aureus for SEM imaging are compared. In order of increasing cooling effectiveness these are: (1) drying in air; (2) plunging in liquid nitrogen; (3) plunging in liquid ethane; and (4) high pressure freezing with liquid nitrogen. These different methods give rise to markedly different biofilm morphologies, which are revealed by cryo-SEM imaging. Significantly, high-pressure frozen biofilms exhibit a rich network of nanoscale ECM fibers surrounding individual bacteria throughout the biofilm thickness. This structure is entirely lost when similar biofilms are dried in air, and it is substantially modified when these biofilms are plunged into liquid nitrogen or liquid ethane.